Avaliação da assistência pré-natal com foco na estrutura do serviço de saúde - SANTOS, John Lennon da Silva (2019)
Prenatal care evaluation is an indispensable tool for managers and health professionals, as they can better identify factors that entail inadequate care, thereby seeking to improve the quality of health actions and structure. The objective of this research was to evaluate the structure of the Health Units (HU) regarding the adequacy for prenatal care to pregnant women cared for in the Primary Care in São Luís – Maranhão, based on the Prenatal and Birth and Humanization Program (PHPN, as per its Portuguese acronym) and on the Rede Cegonha (Stork Network). This is a descriptive research, with a quantitative approach and an evaluative nature, grounded on the Donabedian framework. It was performed in 21 health units of the 7 Health Districts in San Luís – Maranhão that provide prenatal care, where 3 units were chosen per district, determined by random drawing. The research was attended by 21 managers and 40 prenatal health professionals. We performed absolute frequency and descriptive analyzes using the SPSS software, version 12.0 (SPSS Inc., Chicago, United States). The results showed that the structure of the health units was considered satisfactory (52.4%), mainly in relation to human resources, material resources and registration tools. Nevertheless, the presence of weaknesses is still noticeable in the physical plant (14.3%), such as the sufficient availability of meeting rooms and dental offices, the persistence of gaps in access, the timely provision of laboratory tests (47.6%) and the low supply of essential drugs during the gestational period (57%). We can conclude that, despite the good performance of the structure of health services in the Primary Care of São Luís, there are still health inequalities regarding the structural and operational aspects, which must be overcome to provide adequate prenatal care, with a view to meeting what is recommended by PHPN and Stork Network, as well as specific interventions to strengthen Primary Health Care.